2018
DOI: 10.1111/eea.12678
|View full text |Cite
|
Sign up to set email alerts
|

Getting ready for battle: do cabbage seeds treated with jasmonic acid and chitosan affect chewing and sap‐feeding insects?

Abstract: Induced defence allows plants to manage energy reserves more efficiently by synthesizing defence compounds only when needed. A risk of induced defence is that when plants are challenged by herbivores, they may suffer considerable damage before the defence is mounted. Priming can cause a state of readiness for the induction of the defence response, leading to a reduction in the damage received in an energy-efficient and less costly manner. Our objective was to verify whether seed coating with jasmonic acid (JA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It is also conceivable that handling the small delicate insects with a soft paintbrush, despite taking great care, might have had some adverse effects. Baseline mortality of P. xylostella seems to vary considerably between 10 and 43% (Haas et al, 2018; Sun et al, 2018). Nevertheless, both endophyte strains caused a significant decrease in the area of necrotic leaf lesions by S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable that handling the small delicate insects with a soft paintbrush, despite taking great care, might have had some adverse effects. Baseline mortality of P. xylostella seems to vary considerably between 10 and 43% (Haas et al, 2018; Sun et al, 2018). Nevertheless, both endophyte strains caused a significant decrease in the area of necrotic leaf lesions by S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, elicitor-mediated induced resistance has become one of the most challenging research areas in plant herbivory. Recent studies have shown that seeds are receptive to direct application of exogenous phytohormones without being constrained by the inherent costs of defense ( Rajjou et al, 2006 ; Worrall et al, 2012 ; Haas et al, 2018 ). However, research on the beneficial effects of JA seed treatments are restricted to one or only few tomato cultivars ( Smart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in gene expression result, in turn, in the local and systemic production of defense-related metabolites that cause increases in direct and indirect plant resistance to herbivores [13]. The well-established role of JA in induced plant defense has led to the suggestion that the JA pathway can be manipulated to protect crops from their insect pests [46].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that treatment of cabbage seeds, Brassica oleracea , with JA induced resistance to Plutella xylostella L. and Myzus persicae . Resistance was manifested by reduced growth rates and reduced population growth for caterpillars and aphids, respectively [6]. Additionally, a greenhouse study using seed treatments of MJ and JA on several crops including tomato, cowpea, soybean, and wheat, showed a reduction in nematode infection in cowpea and tomato plants [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation